The petrology, geochemistry and petrogenesis of the upper pillow lavas, Troodos Ophiolite Complex, Cyprus - Langdon, George S., 1956- (1982)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1982. Earth Sciences Bibliography: leaves 125-134.